(untitled) (Research, Society and Development, 2020)
Objective: To describe the content found in Brazilian scientific research on the use of ear acupuncture in the stress control of the nursing team. Materials and methods: We used the assumptions of the integrative literature review in the BDENF, LILACS and MEDLINE databases, using the descriptors "acupuncture", auriculotherapy" and "nursing", with articles published from randomized clinical trials published in Portuguese, English and Spanish, with full text available online. We found 11 articles and of these, selected 05 that met the inclusion criteria. Results: From the study of the publications raised, it was possible to construct a table and classify the results of publications into categories: Technique and ear points used to control stress; Difference in results between groups; Auriculotherapy to improve quality of life. Final considerations: The study’s contribution is based on evidence of stress reduction, health promotion and disease prevention with the use of auriculotherapy in the nursing team.